Saneamento rural: estudo de caso na comunidade do Rio Ligação no município de Francisco Beltrão - PR - Campos, Karina Cozer de (2017)
Studying housing and sanitation in rural areas is relevant in view of the persistent Brazilian housing needs demonstrated by the indicators of housing shortage and housing inadequacy in rural settings. Given the importance of sanitation and the harm and problems that lack of sanitation can cause to inhabitants and the environment, specifically in rural areas, the purpose of this research was to prepare a case study on rural housing and sanitation at the Rio Ligação rural community housing units located in the municipality of Francisco Beltrão/PR. Diagnosis of sanitation in the community was conducted taking into account the following aspects: status of the housing in which the dwellers live; community infrastructure; identification of domestic wastewater treatment systems used in the dwellings and the final destination of solid waste, with a discussion of harm caused to health and the environment. The field study involved on-site visits and technical observation. A sewage and water treatment system was implanted by means of a practical activity undertaken with community dwellers. This enabled the provision of information and learning of new techniques that can be replicated in each household. The community is comprised of 46 housing units (HU). Interviews were conducted and questionnaires were administered in 45 HUs. The results of the study show the existence of many HUs in precarious conditions, lack of hygiene, inadequate sanitation facilities, incorrect destination of domestic wastewater and solid waste, lack of treatment of the water consumed by the dwellers, in addition to finding that the Rio Ligação community does not have sufficient basic sanitation, nor public health and education facilities. The conclusion reached is that the community studied needs more sanitation actions aimed at providing its inhabitants with quality of life with regard to basic sanitation, housing, health and environment. It is hoped that this sanitation study will result in the municipal, state and federal-level governments paying more attention to actions and public policies for rural areas, especially for families in less favourable situations, deprived of minimum living and basic sanitation conditions.